Social policy in Brazil (2004-2014): An overview - Patrícia Andrade de Oliveira e Silva (International Policy Centre for Inclusive Growth (IPC-IG), 2017)
Social policy has played a central role in developing countries over the last decade, contributing to a significant decline in poverty and inequality. The objective of this paper is to provide an overview of the evolution of social policy in Brazil, its effects on inequality and poverty, and the implications of the current political and economic scenario regarding the maintenance of its continuous progress. Analyses conducted over the past decade show that negative poverty indicators resulted from a combination of an increase in the value of the minimum wage, a renewed focus on income transfer programmes, and the expansion of assistance projects, old-age pensions and educational and health policies. However, despite these improvements, the current critical economic and political situation (with inflation rates rising in almost every country worldwide) could be quite destructive and demands a concerted strategy to preserve social policy benefits in Brazil. This paper provides a review of recent literature focused on social assistance, social security, health and education, and is divided into six sections. The introduction is followed by an overview of social policy in Brazil. The third section discusses the evolution of poverty and inequality in the country, while the fourth explores the current political and socio-economic situation. The fifth and sixth sections provide the final remarks and bibliographical references, respectively.
Keywords: 330; Social policy; Brazil; 2004; 2014; overview